2020
DOI: 10.1002/ecy.3113
|View full text |Cite
|
Sign up to set email alerts
|

Lignin lags, leads, or limits the decomposition of litter and soil organic carbon

Abstract: Lignin’s role in litter and soil organic carbon (SOC) decomposition remains contentious. Lignin decomposition was traditionally thought to increase during midstage litter decomposition, when cellulose occlusion by lignin began to limit mass loss. Alternatively, lignin decomposition could be greatest in fresh litter as a consequence of co‐metabolism, and lignin might decompose faster than bulk SOC. To test these competing hypotheses, we incubated 10 forest soils with C4 grass litter (amended with 13C‐labeled or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…This apparent discrepancy is most likely the result of the fact that in many of these field studies abiotic mass loss from photochemical mineralization and biotic decomposition occurred simultaneously. During biotic decomposition, lignin content as a proportion of the remaining material increases relative to other more biotically labile organic compounds, which are rapidly degraded by microbial enzymes (Austin & Ballar e, 2010;Hall et al, 2020). Thus, the relative increase in percentage lignin of decomposing litter over time may outpace the photochemical degradation of lignin, such that the percentage change in decomposed litter does not (a) Linear regression for saccharification as a function of lignin content for litter exposed to all doses of solar radiation during the first phase of the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This apparent discrepancy is most likely the result of the fact that in many of these field studies abiotic mass loss from photochemical mineralization and biotic decomposition occurred simultaneously. During biotic decomposition, lignin content as a proportion of the remaining material increases relative to other more biotically labile organic compounds, which are rapidly degraded by microbial enzymes (Austin & Ballar e, 2010;Hall et al, 2020). Thus, the relative increase in percentage lignin of decomposing litter over time may outpace the photochemical degradation of lignin, such that the percentage change in decomposed litter does not (a) Linear regression for saccharification as a function of lignin content for litter exposed to all doses of solar radiation during the first phase of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A subsample of the litter was taken for analysis of potential enzyme activities (described in the section of laboratory analyses), and the remaining material was placed in a 60°C drying oven for 48 h and weighed for determination of mass loss. Ash-free dry mass then was determined for all samples to correct for soil contamination from the field (Harmon et al, 1999) for calculations of organic matter (OM) loss associated with biotic decay.…”
Section: New Phytologistmentioning
confidence: 99%
“…While much is known about C release from plant litter, how these materials are incorporated into soil organic matter (SOM) is not fully understood (Pries et al 2017;Lavallee et al 2018). In recent years, a growing number of studies have shown that recalcitrant compounds (i.e., lignin) are not selectively preserved in decomposing litter (Hall et al 2020) and that labile fractions are the primary source of stable SOM because that strongly control microbial substrate use e ciency (Cotrufo et al 2015). One piece of strong evidence was that nonstructural compounds (i.e., carbohydrates and polysaccharides) are transferred from plant litter into mineral soils during early decomposition (Villarino et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baldrian et al (2016) showed that individual wood logs were dominated by one or a few fungal species. Other information about the quality of the plant material, like lignin concentration, can give more insight in the relationship between the plant quality and decomposition (Hall et al, 2020). In the selected studies, only a limited amount of data was available for such plant traits.…”
Section: Discussionmentioning
confidence: 99%